Sosialisasi Pencegahan Demam Berdarah Dengue Sebagai Proyek Kemanusiaan KKNT Guna Mendukung Program MBKM di Kelurahan Rabangodu Selatan Kota Bima - Kartin Aprianti; Puji Muniarty; Mawar Hidayanti; Muhlis Ade Putra; Tari Juliati; Nurlida Hairin Nafisah (BADAN PENERBIT STIEPARI PRESS, 2023)
Independent Learning Activities Independent Campus Learning (MBKM) in the form of humanitarian projects is a form of learning that trains students to develop social awareness and sensitivity through programmed and institutional activities. The aim of community service activities carried out by KKNT_MBKM STIE BIMA students in the South Rabangodu sub-district is to empower by increasing local community knowledge through socialization on the prevention of dengue fever (DBD). This empowerment is carried out through outreach activities and distributing abate powder to prevent the reproduction of mosquito larvae. This community service activity was carried out well, smoothly and received a positive response from the activity participants. This program was implemented well and participants understood the information on dengue prevention.